Data on the scale insect (Hemiptera: Coccomorpha) fauna of Greece, with description of two new species - Szita, Éva; Fetykó, Kinga Gabriela; Benedicty, Zsuzsanna Konczné; Kozár, Ferenc; Partsinevelos, Georgios; Milonas, Panagiotis; Kaydan, Mehmet Bora (Zootaxa, 2017)
Surveys of the scale insect (Hemiptera: Coccomorpha) fauna of Greece were carried out in 2013 and 2014. Altogether 93 scale insect species were collected, belonging to 11 families. Thirty-eight species (41%) proved to be new to the Greek fauna, including two species new to science (Anophococcus hellenicus Kaydan & Szita sp. n. (Acanthococcidae) and Iberococcus attikus Szita & Fetykó sp. n. (Pseudococcidae)), and two introduced invasive species (Phenacoccus graminicola Leonardi and Pseudococcus comstocki (Kuwana), both Pseudococcidae). The rest of the species seem to be native to the Greek fauna. The total number of scale insect species recorded from Greece is increased to 253.